Predictors of Utilization and Quality Assessment in Robotic Rectal Cancer Resection: A Review of the National Cancer Database. Issue 8 (August 2017) - Buonpane, Christie; Efiong, Enobong; Hunsinger, Marie; Fluck, Marcus; Shabahang, Mohsen; Wild, Jeffrey; Halm, Kristen; Long, Kevin; Buzas, Christopher; Blansfield, Joseph
Robotic surgery (RS) is a novel treatment for rectal cancer resection (RCR); however, this technology is not widely accessible. The objective of this study is to evaluate the utilization of RS in RCR compared with open and laparoscopic techniques and to assess the quality of resection. RCR from 2010 to 2012 were identified using the National Cancer Database and placed into categories: open, laparoscopic, and robotic. A total of 23, 857 patients who received open, laparoscopic, and robotic RCR were included (n = 14, 735 (61.8%); 7, 185 (30.1%); 1, 937 (8.1%), respectively). Patients over 70 had a lower likelihood of robotic RCR. Patients with insurance were 2 times more likely to have robotic RCR. Patients at an academic/research program were more likely to undergo RS compared with a community cancer program (OR 3.6, 95% CI [2.79, 4.78]; P < 0.0001). Length of stay (LOS) was longer in open (7.9 ± 7.1) versus laparoscopic (6.6 ± 6.3) or robotic (6.8 ± 6.4) RCR (P < 0.0001). Although there was an increased likelihood of positive surgical margins with open RCR (OR 1.3, 95% CI [1.09, 1.66]; P < 0.0001), there was no difference in robotic and laparoscopic techniques. Younger insured patients at academic/research affiliated hospitals have a higher likelihood of receiving robotic RCR. Compared with open RCR, robotic RCR have a lower likelihood of positive surgical margins and shorter LOS.